Effect of Exogenous Melatonin and Different Photoperiods on Differential Leucocyte Count in Chhotanagpuri Ewe - Choudhary, Pankaj K.; Kumar, Pramod; Maurya, Pankaj K.; Kumar, Mukesh; Ishwar, Ajay K.; Kumar, Rajesh; Niyogi, Debasish (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
Forty-two healthy, non-pregnant, non-lactating Chhotanagpuri ewe, having body weight ranging from 14.11 ± 0.09 to 15.38 ± 0.06 kg,were selected and isolated from rams 2 months before melatonin administration. The selected animals were allocated randomly intoseven groups each of 6 animals, viz., Group-I [Normal control], Group-II [Long day (LD) control], Group-III [LD + melatonin administration3 mg/day orally], Group-IV [(LD + melatonin administration s/c @ 1 mg/day], Group-V [Short day (SD) control], Group-VI [SD + melatoninadministration 3 mg/day orally] and Group-VII [SD + melatonin administration s/c @ 1 mg/day]. Rams were then introduced intoeach group after completion of exogenous administration of melatonin for one month. Blood samples without anticoagulant in vialswere collected from each animal at day-0 (a day before the start of experiment), 30th, 60th, 90th, 120th and 150th of the experiment.Among different periods, lymphocyte % in the third and fourth months of the experiment was significantly (p
Keywords: Chhotanagpuri Ewe; Differential leucocyte count; Exogenous Melatonin; Photoperiod